2004
DOI: 10.1016/s0896-6273(04)00077-7
|View full text |Cite
|
Sign up to set email alerts
|

SNAP-25 Modulation of Calcium Dynamics Underlies Differences in GABAergic and Glutamatergic Responsiveness to Depolarization

Abstract: SNAP-25 is a component of the SNARE complex implicated in synaptic vesicle exocytosis. In this study, we demonstrate that hippocampal GABAergic synapses, both in culture and in brain, lack SNAP-25 and are resistant to the action of botulinum toxins type A and E, which cleave this SNARE protein. Relative to glutamatergic neurons, which express SNAP-25, GABAergic cells were characterized by a higher calcium responsiveness to depolarization. Exogenous expression of SNAP-25 in GABAergic interneurons lowered calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
158
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(179 citation statements)
references
References 41 publications
14
158
5
Order By: Relevance
“…These data agree with the assumption that the SNARE mechanisms largely characterize the excitatory synapses and that glutamate-containing vesicles release their content via SNARE-dependent mechanisms [12,15,33,34]. However, this study demonstrates subpopulations of glutamatergic synapses in the cerebellar cortex that do not contain the examined SNARE proteins.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These data agree with the assumption that the SNARE mechanisms largely characterize the excitatory synapses and that glutamate-containing vesicles release their content via SNARE-dependent mechanisms [12,15,33,34]. However, this study demonstrates subpopulations of glutamatergic synapses in the cerebellar cortex that do not contain the examined SNARE proteins.…”
Section: Discussionsupporting
confidence: 89%
“…This observation largely agrees with the assumption that SNAP-25 independent exocytotic pathways exist to support neurotransmission in GABAergic synapses [12,33], even if this assumption is not accepted by some researchers [14]. Moreover, it should again pointed out that some GABAergic axon terminals of basket neurons are exceptions to this assumption.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…56 By taking advantage of mixed cultures of wt and Het neurons, we demonstrated that postsynaptic defects in In recent years SNARE/SM proteins have been shown to be involved in activity-dependent AMPA receptor exocytosis during LTP 22 and SNAP-25, in particular, has been reported to have a role in the removal of kainate receptors from the postsynaptic membrane, 57 in the insertion of NMDA receptors in neuronal plasma membrane 21 and of P/Q and L typevoltage gated calcium channels. 10,58 Also, acute regulation of SNAP-25 expression has been found to impair synaptic plasticity probably affecting NMDAR trafficking. 22 Our data indicate that SNAP-25 has also a structural role in the postsynaptic compartment by interacting with the postsynaptic protein p140Cap, which in turn binds to PSD-95.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the calcium levels by chelators induces a higher sensitivity of GABA-ergic neurons to BoNT/A action (Grumelli et al, 2010;Verderio et al, 2004).…”
Section: Preferential Effect On Excitatory Vs Inhibitory Neuronsmentioning
confidence: 99%